SOUNDS LEARNING USING TEAMS GAMES TOURNAMENT WITH FLASH CARD AS MEDIA AT THE 13th JUNIOR HIGH SCHOOL OF MAGELANG - Lestari, A.; Widiyatmoko, A.; Alimah, S.; Juliyani, I. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2015)
The aim of this research is to know about studentsâ response and the effectiveness of Teams Games Tournament learning model with Flash Card as media. This research type is Quasi Experimental Nonequivalent Group Design. The subject of the study is the students of 8 E and 8 F of the 13th junior high school of Magelang. The result of cognitive assessment showed that the classical learning achievement was 87% and the gained score was 0.46 which is included in media category. Value of Sig. (2-tailed) of Mann-Whitney U-Test is 0.01. It means that there is the significant difference of academic achievement between the experiment group and the control group. The result of affective and pshycomotoric assessments are included in good category at average score 75% and 71%. Correlation among cognitive, affective, and psychomotoric learning achievements was strong at R Score 0.684. Studentsâ response toward the learning showed average score at 74%, and it was included in good category. Based on the result, Teams Games Tournament learning model with Flash Card as media in learning about sounds at the 13th junior high school in Magelang is effective towards the learning achievement and the responses of the 8 D graders towards the learning is categorized good.